Strategy for Developing SMEs Based on Local Potentials: Case Study in The District of Sleman, Yogyakarta - Suyatno,; Suryani, Dewi Amanatun (Advances in Social Sciences Research Journal, 2023)
The aim of this study is to describe the strategy for developing MSMEs based on local potentials to enhance and develop the people’s economy and welfare in Girikerto Village, Turi, District of Sleman.This study uses a descriptive qualitative research methodology; The object of this research is MSMEs in the Village of Girikerto, The Kapanewonan Turi; Primary data are obtained from an interview, field note, observation, and FGD with the stakeholders; Secondary data are taken from the Profile of Girikerto Village, Central Statistics Bureau, The Office of Cooperatives and Small Scale Enterprises of the District of Sleman. Special Region of Yogyakarta. Findings of the research is that the strategy for developing MSME based on local potentials, begin with the assessment of the local potential to develop involving stakeholders guided by the government to formulate policies and programs, provide facilitation, and develop activities in collaboration with related institutions, business, and universities by empowering creative and innovative human resources to process into competitive and value-added products. This study contributes to the concept of formulating a strategy for developing MSMEs based on the local potential to strengthen the community’s economy. This study can help the government to promote and develop the program and policy in developing MSME based on the local potential to enhance the communities’ economy and welfare. The Research is limited in developing MSME based on local potentials in the Village of Girikerto, Turi